(untitled) (GESTIÓN Y TENDENCIAS, 2021)
Bloomberg’s Covid-19 Resilience Ranking[1] recognizes New Zealand as the country with the best response in the world to the crisis caused by the pandemic. This article explores the innovative initiatives introduced in New Zealand from the perspective of social and inter-organizational collaboration in confronting the pandemic. The New Zealand experience opens up an opportunity for new lessons in Latin American countries.